Luminescent properties of LiF:Mg, Cu, P detectors irradiated by the 10-MeV electrons. Issue 9 (3rd October 2017) - Maslyuk, V. T.; Megela, I. G.; Obryk, B.; Vieru-Vasilitsa, T. O.
ABSTRACT: In this study, the effect of intensity and irradiation dose of mixed 10-MeV gamma-electron beam and braking (Bremsstrahlug) radiation of gamma-quanta beam with the electron fluence range of on the luminescent properties of the TLD-100H detectors has been studied. The long-term phosphorescence of the samples has been established; was found it dependent on irradiation intensity and dose at room temperature. The mechanism of influence of radiation defects on the luminescent properties of irradiated a materials is discussed too.